Enhancing Students' Interest in Reading and Improving Their Literacy Skills through The Implementation of A Reading Literacy Program - Anasari, Safitri; Rahmawati, Laili Etika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: In this research, the objective used is to implement a reading libration program to increase reading interest and reading skills of class VIII students at Nurul Islam Ngemplak Middle School, as well as increasing reading interest and reading skills of class VIII students through a reading libration program at Nurul Islam Ngemplak Middle School. Methodology: In this research, the method used is Classroom Action Research (PTK), the concept of classroom action research according to Kurt Lewin consists of four components, namely planning, action, observation and reflection. Classroom action research is carried out to improve the conditions of a lesson that can be observed directly when learning in class. The setting of this research was carried out in class VIII of Nurul Islam Ngemplak Middle School, Ngemplak District, Boyolali Regency, Central Java. The research was carried out for two months, namely in August and September. This research was carried out in two cycles, each cycle being carried out twice. Results: The results of the classroom action research that has been carried out show that in cycle II the reading interest of class VIII students has seen a significant increase, this is proven by the test scores taken. Apart from that, students' reading skills are also starting to look good and are improving as evidenced by the routine activity of reading fable texts. Applications/Originality/Value: The validity test used in this research is triangulation, the researcher uses data source triangulation and method triangulation. Triangulation of data sources was obtained from several data sources, namely students, educators and school principals. And triangulation methods are used by researchers to search for data directly through field observations, interviews and tests to measure students' reading abilities.